Examining the factors influencing undergraduate students’ use of digital arts playrooms in South African university game studies programs - Randle, Oluwarotimi; Oyetade, Kayode (African Perspectives of Research in Teaching and Learning Journal (APORTAL), 2025)
Integrating digital arts playrooms into education provides an innovative opportunity to enrich creative learning for 21st-century students, notably within game studies. While digital tools and interactive spaces are gaining attention globally, there is limited research that specifically explores the dynamics of these innovative resources. This study seeks to examine the factors influencing students' utilization of digital arts playrooms as an innovative educational resource. To guide this exploration, the study employs the Unified Theory of Acceptance and Use of Technology as the theoretical framework, which helps identify key determinants of technology adoption. The study adopts a survey-based quantitative research design, utilizing data collected from 279 South African university students who have prior experience or exposure to the digital arts playroom. The research design involved demographic analysis, exploratory factor analysis, and regression analysis to identify significant predictors of usage. The findings reveal that effort expectancy, social influence, and facilitating conditions are significant predictors of digital arts playroom utilization, emphasizing the importance of these factors in shaping student engagement with digital art platforms. However, it was found that performance expectancy does not influence usage, possibly due to the novelty of the technology. This research contributes to educational practices by providing practical insights for enhancing creative learning experiences in game studies programs. By aligning theoretical perspectives with practical applications, the study advances the integration of digital tools in education, offering guidelines for educators and policymakers to effectively foster engagement with digital technologies.
Journal article published in African Perspectives of Research in Teaching and Learning Journal Issue 1, Volume 9, 2025
Keywords: 21st-century Learning; Digital Arts Playroom; Educational Technology; Game Studies Program; Student Engagement; Technology Novelty; Computer graphics; Service learning; Educational technology; Novelties